Značilnosti opravljanja sečnje in spravila v zasebnih gozdovih v Sloveniji - Ščap, Špela (Acta silvae et ligni, 2021)
A survey conducted in 2019 covered 544 randomly selected forest owners. More than half of the forest owners own a forest estate ranging from 1 to 4.99 ha. For 62 % of respondents, the primary purpose of forest management is to harvest wood for their own needs. In 2015%2019, 71 % of respondents carried out felling and skidding in their forests. In total, approximately 50,000 m3 of wood was felled (24 m3 /ha or 141 m3 per holding). The largest volumes were felled by private owners with small forest holdings (up to 0.99 ha), on average 41.4 m3 /ha. There were statistically significant differences between the size of the forest holding and the average volume of annual felling. Furthermore, there were no statistically significant differences in felling intensity between male and female forest owners. The survey found that professional contractors carried out 41 % of felling and harvesting. Furthermore, there were significant differences between the size of the private forest estate and the method of performing forest operations. The results showed that the largest share of private owners who carry out all felling and skidding with the help of hired contractors is in the size class of forest holdings from 5 to 9.99 ha. The study did not confirm statistically significant differences in the intensity of felling between male and female private forest owners.
Keywords: anketa; felling; forest estate; forest operations; gozdna posest; intensity of felling; intenziteta sečnje; private forest owners; privately owned forests; questionnaire; sečnja; skidding; spravilo; structure of forest owners; struktura lastnikov; zasebni gozdovi; zasebni lastniki